2022
DOI: 10.21203/rs.3.rs-1427548/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Interaction Between Autophagy and Epithelial-Mesenchymal Transition via NICD/ULK1 is Involved in the Formation of Diabetic Cataracts

Abstract: BackgroundCataracts are the leading cause of blindness and a common ocular complication of diabetes. Epithelial-mesenchymal transition (EMT) of lens epithelial cells (LECs) and altered autophagic activity occur during the development of diabetic cataracts. The disturbed interaction of autophagy with EMT in LECs stimulated by high glucose may participate in cataract formation.MethodsWe employed a diabetic rat model induced by streptozotocin (STZ) and human lens epithelial HLE-B3 cells stimulated with high gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recent investigations underscored the pivotal function of autophagy in fostering TGF-β2-induced EMT in lens epithelial cells. A novel study in the context of diabetic cataracts revealed that elevated glucose levels induced EMT in lens epithelial cells through the activation of Jagged1/Notch1/NICD/Snail signalling and inhibition of autophagy via the AKT/mTOR/ULK1 pathway (67). miR-429 has been confirmed to play a significant role in various physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations underscored the pivotal function of autophagy in fostering TGF-β2-induced EMT in lens epithelial cells. A novel study in the context of diabetic cataracts revealed that elevated glucose levels induced EMT in lens epithelial cells through the activation of Jagged1/Notch1/NICD/Snail signalling and inhibition of autophagy via the AKT/mTOR/ULK1 pathway (67). miR-429 has been confirmed to play a significant role in various physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%